Backstepping Robust H∞ Control for a Class of Uncertain Switched Nonlinear Systems Under Arbitrary Switchings. Issue 1 (14th March 2012) - Ma, Ruicheng; Dimirovski, Georgi M.; Zhao, Jun
Abstract This paper addresses global robust H∞ control for a class of switched nonlinear systems with uncertainty under arbitrary switchings. Each subsystem is in lower triangular form. The uncertainties are assumed to be in a known compact set. The backstepping design technique is used to design a smooth state feedback controller that renders the associated closed‐loop switched system globally robustly asymptotically stable and imposes a pre‐specified upper bound to the L2‐gain under arbitrary switchings. An example is provided to demonstrate the efficacy of the design approach.